Outcomes to measure the effects of pharmacological interventions for pain management for women during labour and birth: a review of systematic reviews and randomised trials. (20th December 2021) - Tan, A; Wilson, AN; Eghrari, D; Clark, H; Tse, WC; Bohren, MA; Homer, CSE; Vogel, JP
Abstract : Background: Pharmacological pain management options can relieve women's pain during labour and birth. Trials of these interventions have used a wide variety of outcomes, complicating meaningful comparisons of their effects. To facilitate better assessment of the effectiveness of labour pain management in trials and meta‐analyses, consensus about key outcomes and the development of a core outcome set is essential. Objective: To identify all outcomes used in studies of pharmacological pain management interventions during labour and birth. Design: A review of systematic reviews and their included randomised controlled trials was undertaken. Search strategy: Cochrane CENTRAL was searched to identify all Cochrane systematic reviews describing pharmacological pain management options for labour and birth. Search terms included 'pain management', 'labour' and variants, with no limits on year of publication or language. Selection criteria: Cochrane reviews and randomised controlled trials contained within these reviews were included, provided they compared a pharmacological intervention with other pain management options, placebo or no treatment. Data collection and analysis: All outcomes reported by reviews or trials were extracted and tabulated, with frequencies of individual outcomes reported. Main results: Nine Cochrane reviews and 227 unique trials were included. In total, 146 unique outcomes were identified and categorised into maternal, fetal, neonatal, child, health service, provider's perspective or economic outcome domains. Conclusions: Outcomes of pharmacological pain management interventions during labour and birth vary widely between trials. The standardisation of trial outcomes would permit the assessment of meta‐analyses for best clinical practice. Tweetable abstract: Outcomes to measure pharmacological pain management options during labour are highly variable and require standardisation. Tweetable abstract: Outcomes to measure pharmacological pain management options during labour are highly variable and require standardisation.